DESIGN AND IMPLEMENTATION OF AN ANALYSIS TOOL FOR UNSTRUCTURED SIMUATION OUTPUTS - Lee, Kangsun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
As simulations have becomewidely used in the analysis ofcomplex systems, more engineers are experiencing difficulties in managing massive amounts of unstructured datasets. While conventional database management systems have facilitated the simulation analysis process by storing datasets in time-tagged databases and querying the databasesto answer analysis questions, their usehas been partly limited due to the following two reasons: 1) insufficient mechanisms to handle unstructured datasets; and 2) tight coupling to specific platforms and devices in delivering the analysis results. In this paper, we present R-Logger (Responsive-Logger), a plugin softwareto aid in simulation analysis tasks for unstructured simulation logs. Once plugged into a simulator, R-Logger is able to 1) filter out the desired datasets from the unstructured simulation logs; 2) store them in the server-side database; 3) analyze them by utilizing built-in queries, and 4) deliver the analysis results over the Web. R-Logger is able to respond to the user’s environment and dynamically change the layout of the analysis results to fit into various devices, including desktops, tablets, and mobile phones.